2004
DOI: 10.1007/bf02931638
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acetic acid, citric acid, and trisodium citrate in combination with different levels of water activity on the growth ofArcobacter butzleri in culture

Abstract: The influence of weak organic acids and trisodium citrate in combination with a high or a reduced water activity (aw) was investigated when a population of Arcobacter butzleri was exposed to a low concentration of acetic or citric acid, and trisodium citrate combined with high (0.993) and reduced (0.977) aw in culture broth at 30 degrees C. Regardless of water activity, acetic and citric acid (> 0.2%) inhibited the growth of A. butzleri with no viable cells detected after 4-5 h of incubation. Enhanced survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Another reason could be that the addition of NaCl (to decrease aw) under certain acetic acid conditions exerted a protective effect on the ATSSB spores. A similar phenomenon was observed by Cervenka et al (2004), who reported that a decrease in aw (0.993 to 0.977) enhanced the antimicrobial effect of 0.1% (w/v) acetic acid on a food-borne pathogen (Arcobacterbutzleri), while the same aw change resulted in an adverse effect when 0.2 and 0.3% acetic acid was present.…”
Section: Influence Of Water Activitiessupporting
confidence: 81%
“…Another reason could be that the addition of NaCl (to decrease aw) under certain acetic acid conditions exerted a protective effect on the ATSSB spores. A similar phenomenon was observed by Cervenka et al (2004), who reported that a decrease in aw (0.993 to 0.977) enhanced the antimicrobial effect of 0.1% (w/v) acetic acid on a food-borne pathogen (Arcobacterbutzleri), while the same aw change resulted in an adverse effect when 0.2 and 0.3% acetic acid was present.…”
Section: Influence Of Water Activitiessupporting
confidence: 81%
“…2005). Concentrations of organic acids (>0·2% acetic and citric acid) used widely in meat decontamination processing represent feasible tools for reducing A. butzleri contamination (Cervenka et al. 2004).…”
Section: Antimicrobial Studiesmentioning
confidence: 99%
“…2004). Regardless of water activity ( A w ), at high (0·993) and reduced (0·977) A w , acetic and citric acid (>0·2%) inhibited the growth of A. butzleri with no culturable cells detected after 4–5 h of incubation (Cervenka et al. 2004).…”
Section: Antimicrobial Studiesmentioning
confidence: 99%
See 1 more Smart Citation